Factors influencing smoking behaviour changes during Ramadan among Malay male students - Ismail, Suriani; Mohd Zulkefli, Nor Afiah; Cheong, Sau Chung; Zainal, Mohamad Sulaiman (Mashhad University of Medical Sciences, 2015)
Introduction: Fasting during Ramadan provides an opportunistic setting for smoking cessation intervention. Smokers find it easy to cease smoking during Ramadan due to the religion, cultural and environmental influences. This study aims to determine the changes in smoking behaviour during Ramadan among Malay Muslim male students who were current smokers. Methods: This is cross sectional study using self-administered questionnaire to evaluate the socio demographic characteristics and two main relevant religious perceptions on smoking (i.e. ‘Is smoking ‘haram’ and ‘Does smoking invalidate your fasting’). Fagerstrom Test for Nicotine Dependence (FTND) questionnaire was used to evaluate smoking behaviour before and during Ramadan. The total FTND scores and the percentages according to FTDN items, before Ramadan and during Ramadan were compared to determine good or poor smoking behaviour changes. Results: The overall FTND scores and the percentage according to its items were significantly reduced. There were significant association between smoking behaviour changes during Ramadan and household income, nicotine dependence and perception that smoking is ‘haram’. The percentage of good smoking behaviour changes was higher among those with higher income, high nicotine dependence and those who are not aware that smoking is ‘haram’. Conclusion: There is a great potential in taking advantage of the Ramadan environment to encourage smoking cessation among Muslim smokers.